Imprensa, política e publicidade: Um estudo sobre a revista Caros Amigos (1997-2006) - Fiorucci, Rodolfo [UNESP] (UNISINOS - Universidade do Vale do Rio Dos Sinos, 2011)
The article discusses the relationship between media, politics and advertising in the magazine Caros Amigos between 1997 and 2006. It studies on the weight of the Partido dos Trabalhadores in the funding of the publication and the charges made against the magazine's publishers due to this fact. © 2011 by Unisinos.
Press, politics and advertising: A study on the magazine Caros Amigos (1997-2006)
Keywords: Advertising; Caros Amigos; Partido dos Trabalhadores